Hidden in the Chest: Myocardial Bridging and Cardiovascular Response to Exercise - Kret, Dominik; Szlachta, Wiktoria; Twardowska, Daria; Tłoczek, Wiktoria; Śliwa, Wiktoria (Quality in Sport, 2026)
Myocardial bridging (MB) of the coronary arteries has long been considered a benign anatomical variant with no significant clinical relevance. However, the development of modern imaging and functional diagnostic methods indicates that its impact on myocardial perfusion may become apparent under conditions of increased hemodynamic load, especially during physical exertion. In the context of sports science, this issue is particularly important, as even subtle coronary flow disturbances can modulate the heart's response to training load and affect exercise tolerance.The aim of this study was to present the current state of knowledge on the anatomy, pathophysiology, clinical picture, diagnosis, and therapeutic management of myocardial bridges, with particular emphasis on their functional significance under conditions of stress typical of physical activity. The article is a narrative review of the literature based on a critical analysis of anatomical, observational, and imaging studies, as well as works devoted to functional assessment and treatment strategies. Available data indicate that MBs are a common structure, but heterogeneous in terms of morphology and hemodynamic significance. Although they remain asymptomatic in most people, in selected cases they may be associated with myocardial ischemia, arrhythmias, and reduced exercise tolerance. Myocardial bridges require individualized clinical and functional assessment, and their presence should not be automatically considered insignificant, especially in the context of exercise capacity assessment.